Исповедь на заданную тему - Ельцин Борис Николаевич (Молодежный центр "Спектр", 1990)
Экземпляры: КХ (20170203) / Инвентарный номер: 967357 / Цена: 5.00 / Сис.шифр: 66.3(2) / Авт.знак: Е 58 / ГРНТИ: 11 / ББК: 63.3(2)64